Association of Acute Postoperative Pain and Cigarette Smoking With Cerebrospinal Fluid Levels of Beta-Endorphin and Substance P - Wang, Fan; Li, Hui; Mu, Qingshuang; Shan, Ligang; Kang, Yimin; Yang, Shizhuo; Chang, Hui-Chih; Su, Kuan-Pin; Liu, Yanlong (Frontiers in Molecular Neuroscience, 2022)
Objective: Cigarette smoking has shown to be associated with postoperative pain perception which might be mediated by beta-endorphin (BE) and substance P. However, those effects on postoperative pain perception has never been investigated in human cerebrospinal fluid (CSF), which is known as an optimal medium to reflect biochemical alterations in human brain. Therefore, we investigated the association among cigarette smoking, postoperative pain, BE and substance P levels using human CSF. Methods: A total of 160 Chinese male subjects (80 active smokers and 80 non-smokers) who would undergo lumbar puncture before surgery of anterior cruciate ligament reconstruction were recruited and 5ml-CSF samples were collected. Pain visual analogue scale (VAS) scores, post anesthetic recovery duration (PARD), and smoking variables were obtained. CSF levels of BE and substance P were measured. Results: Compared to non-smokers, active smokers had significant higher pain VAS scores (2.40 ± 0.67 v.s. 1.70 ±0.86, p＜0.001) and PARD (9.13 ± 2.11 v.s. 7.27 ±1.35, p = 0.001), lower CSF BE (33.76 ± 1.77 v.s 35.66 ± 2.20, p = 0.001) and higher CSF substance P (2124.46 ± 217.34 v.s. 1817.65 ± 302.14, p < 0.001) levels. Pain VAS scores were correlated with PARD in active smokers (r=0.445, p = 0.002). Conclusion: Cigarette smoking was associated with increased postoperative pain intensity, shown by delayed pain perception, higher pain VAS scores, and lower BE and higher substance P levels in CSF of active smokers. Moreover, the longer postoperative pain perception was delayed, the more pain intensity was increased.